1996
DOI: 10.1002/(sici)1097-0215(19960117)65:2<134::aid-ijc2>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the major histocompatibility complex on age at onset of chronic lymphoid leukaemia

Abstract: The major histocompatibility complex is one of the interactive factors in the multifactorial model of carcinogenesis. Its main influence in experimental models is on the age at onset of malignancies. We have previously shown a similar effect of homozygosity for HLA-DR53 in CML. In the present study, we investigated 79 patients with CLL and 329 local controls from Germany. In addition to full serotyping, all patients and I I 6 of controls were also typed by HU-DR6 PCR analysis. The homozygosity rates for DR53 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…For the haplotype HLA-DRB1*0401:DRB4*0103, a CLL-specific linkage disequilibrium together with an increased haplotype frequency were observed. In accordance with the observation of Dorak et al, 16 these findings can be interpreted as a positive association of CLL with the HLA-DR4:DR53 haplotype.…”
Section: Haplotype Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…For the haplotype HLA-DRB1*0401:DRB4*0103, a CLL-specific linkage disequilibrium together with an increased haplotype frequency were observed. In accordance with the observation of Dorak et al, 16 these findings can be interpreted as a positive association of CLL with the HLA-DR4:DR53 haplotype.…”
Section: Haplotype Analysissupporting
confidence: 91%
“…An association of HLA-DRB1*0401 and -DRB4(DR53) with CLL had been suggested in a previous study based on PCR-SSO and serologic typing. 16 Due to the different typing techniques compared with our present study, these results did not represent an a priori hypothesis, and correction with the total number of alleles was necessary. With the large number of known HLA alleles, a lack of significance after correction is a common problem of studies investigating disease association of polymorphic genes.…”
Section: Haplotype Analysismentioning
confidence: 68%
See 1 more Smart Citation
“…These polymorphic antigens could also influence the pathogenesis of B-cell or T-cell malignancies through continuous clonal stimulation of antigen-specific lymphocytes [16]. Many studies examined the possible association of the HLA system with lymphoproliferative disorders, but few reported HLA frequencies in CLL [17][18][19][20][21][22][23][24]. Furthermore, the frequency of HLA alleles has not been well determined in Asian CLL patients.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some studies indicated no association of CLL with HLA molecules [24], others demonstrated association with a variety of HLA alleles [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%